2019
DOI: 10.1002/hlca.201900046
|View full text |Cite
|
Sign up to set email alerts
|

Small Cage Uranofullerenes: 27 Years after Their First Observation

Abstract: The tetravalently stabilized fullerene cage of C28 is historically the most elusive small fullerene cage observed by employing the laser vaporization synthesis methodology. Its first observation reported by Smalley et al. in 1992 suggests that C28 is potentially the smallest and most stable fullerene ever observed. By using the Krätschmer−Huffman arc discharge synthesis method, we have recently succeeded in synthesizing a series of uranium‐endohedral fullerenes which differ from those reported by Smalley and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
1
7
1
2
Order By: Relevance
“…the smaller the carbon cage the larger the formal transfer to get the M@C 2n stabilized. 12 Other gas-phase detections of uranofullerenes 13,14 and computational studies on the U-cage interaction in small cages 15,16 or U-U bond in U 2 @C 60 have been reported. 17 However, it was not until 2017 that the first actinidofullerene was synthesized by an arc-discharge method and fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…the smaller the carbon cage the larger the formal transfer to get the M@C 2n stabilized. 12 Other gas-phase detections of uranofullerenes 13,14 and computational studies on the U-cage interaction in small cages 15,16 or U-U bond in U 2 @C 60 have been reported. 17 However, it was not until 2017 that the first actinidofullerene was synthesized by an arc-discharge method and fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In the early work of Smalley and co-workers, it was already shown that in addition to several small and medium-sized mono-uranium endofullerenes, 38,39 small diuranium endofullerenes, such as U 2 @C 58 and U 2 @C 52 , could also be detected by mass spectrometry. Without a strong metal−metal interaction, it is very difficult to understand that such dimetallic fullerenes can be formed and grow at the very high temperatures at which these compounds are synthesized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the early work of Smalley and co-workers, it was already shown that in addition to several small and medium-sized mono-uranium endofullerenes, , small diuranium endo-fullerenes, such as U 2 @C 58 and U 2 @C 52 , could also be detected by mass spectrometry. Without a strong metal–metal interaction, it is very difficult to understand that such dimetallic fullerenes can be formed and grow at the very high temperatures at which these compounds are synthesized. , In the present paper, we report Car–Parrinello MD simulations in combination with DFT and CASPT2 calculations to evaluate under which conditions, if any, the formation of covalent bonds between two U ions within fullerenes is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Дальнейшие исследования показали, что фуллерен С 28 является нестабильной молекулой, которая стабилизируется при образовании эндофуллеренов M@С 28 с элементами Zr, W, Mo, Os, Ti, Th, U, Ce, которые способны принимать электронные конфигурации M 4+ [4]. Исследованию свойств фуллерена С 28 посвящено довольно много работ [5][6][7][8].…”
Section: Introductionunclassified
“…Из диаграммы Шлегеля, изображенной на рис. 1, видно, что фуллерен С 28 с группой симметрии T d содержит три неэквивалентных связи, которые обозначены через a, b и c; и три группы неэквивалентных атомов углерода: G 1 = {1, 3, 5, 9, 13, 17, 19, 20, 22, 23, 25, 26}, G 2 = {2, 4,6,8,10,12,14,16,18,21,24, 27}, G 3 = {7, 11, 15, 28}. Связь а связывает между собой два пентагона, связь b связывает пентагон и гексагон, а связь с связывает между собой два гек-сагона.…”
Section: Introductionunclassified